One asymptotical estimate for sums of independent random values in the Banach space - Matsak , I. K. (Ukrains’kyi Matematychnyi Zhurnal, 2025)
A number of estimates are established for the probability of large deviations of sums of independent random variables in a Banach space. In the one dimensional case inequalities of this type occur in the familiar inequalities of Nagaev and Fuk.